PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI DIGITAL PREZI UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PEMBELAJARAN IPS KELAS V - Rosalinda; Ira Restu Kurnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The development of Prezi learning media was carried out based on a problem found at SDN Jayabakti 03, namely the lack of teachers in utilizing learning media. As a result of the lack of use of learning media, it causes a decrease in students' interest in learning. The aim of the research is to develop learning media based on the Prezi digital application to increase students' interest in learning. The method for developing media uses Research and Development using the ADDIE design in media development. The results obtained from the validation of learning media obtained an average of 90% with the criteria